The Urgency of Oral Corrective Feedback in English Language Teaching: Students and Teachers’ Perception - Eulis Rahmawati (Yayasan Karinosseff Muda Indonesia, 2023)
Oral corrective feedback plays a significant role that cannot be ignored in second and foreign language learning. The objectives of the research is to reveal the urgency of oral corrective feedback in the English instruction. It further aims at providing guidance toward English instruction practice at secondary school. This research provides a clear description of feedback on English language teaching, especially how teachers give feedback and how students perceive and interpret the feedback given. The research was conducted in one of secondary schools in Kota Serang. In relation to this, the respondents of the research are English teachers and students at the second grade of secondary school. The data were collected through observation, interview, and questionnaire. It was found that the teacher gave oral corrective feedback immediately and delayed depend on the situation, focus on certain topics and collaboratively. The results revealed that students generally have good perception of oral corrective feedback. They like to be corrected when they made a mistake